The Japanese Beetle and its Control - Hadley, C. H. (United States. Department of Agriculture, 1940)
Journal number 1856 in the Farmers' Bulletin series published by the United States Department of Agriculture. The article describes the Japanese beetle, a pest brought to the United States from Japan, including its seasonal history, harmful habits, and the methods found useful in destroying the insect or preventing injury to crops and plants. The work includes both black and white and color illustrations. This issue was contributed to by the United States Bureau of Entomology and Plant Quarantine. Work is digitized in its entirety.
Keywords: United States. Bureau of Entomology; United States. Department of Agriculture; Japanese beetle; Japanese beetle--Control; Insect pests; Pests--Control; Entomology